PREVENTION OF DENTAL CARIES THROUGH DENTAL HEALTH EDUCATION AND UTILIZATION OF MARINE PRODUCTS AT ELEMENTARY SCHOOL MUHAMMADIYAH 9 SURABAYA - Pinasti, Restika Anindya; Pangabdian, Fani; Damayanti, Nurul (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Muhammadiyah 9 Elementary School, Surabaya, is geographically located on the coast, so it is often referred to as Bahari Muhammadiyah 9 Elementary School. Based on preliminary survey results, Muhammadiyah 9 Elementary School students frequently consume cariogenic foods, resulting in a high caries index of 4.6. From an educational perspective, the learning method is still relatively conventional and does not align with the "Merdeka Belajar" curriculum, resulting in hampered learning and a lack of student knowledge about maintaining health, especially dental and oral health. Furthermore, the implementation of school dental health activities has not been optimal. Community service methods are carried out through several stages: outreach, training, mentoring and evaluation, and a desire program. The participation of the university community in helping solve the problems facing the community in such environments is essential by providing education and regular dental and oral health checks to reduce the caries index, as well as providing snacks such as sea cucumber jelly candy and anchovy cookies made from seafood, which have anti-cariosis properties. The use of seafood as an alternative to prevent dental caries shows very promising potential. Program Pengabdian kepada Masyarakat Bima 2025: This program has succeeded in raising student awareness of the importance of maintaining dental hygiene and introducing innovative and natural ways to prevent caries.